Total Energy Management Of A University Engineering Building Through Audit - Shezad, Zaeem (2019)
As the demand for energy use is growing day by day and the need for good indoor environment quality has been motivated to find the alternative way to find the solution for energy efficiency for all the indoor activity and electrical consumption. In this study, different attempts have been made to measure and evaluate the existing conditions of the Fakulti Kejuruteraan Elektrik (FKE) which is located in the main campus of UTeM. Some physical parameters for the energy consumption were measured which include, operating temperature, air velocity, relative humidity, lighting intensity and air flow which were compared to the current Malaysian standards for building (Malaysian Standard 1525: 2014). This project results were gathered by the physical parameter which were collected with the electronic instrument which includes lux meter, air velocity meter and temperature and the results were compared with the Malaysian standards, for instance the results are based on the survey which was done for couple of days to collect all the required data from 9:00 am to 5:00 pm in the FKE building block D and E, the average temperature which was recorded for all the levels is ranging from 21 — 26 (°C) which is within the Malaysian standard MS 1525:2014 (23-26 °C). The average relative humidity was ranging from 51% to 57% and is within the standard followed by the air velocity 0.3 — 0.5 m/s. The average lighting intensity was recorded was ranging from 0.3m/s to 0.5m/s Lux. In addition to this, the Building Energy Index (BEI) for 2017/2018 is 134.37 kWh/m?/year which is slightly. lower if compared to the MS 1525:2014 standard which is 135 kWh/m?/year. Finally all these physical analysis was done and compared with the Malaysian standard some of them were satisfying and those results which were not matching to standard or how can we improve the results, some important suggestion like retrofit were suggested on how to conserve energy measure in terms of replacement of lamps and installation of new ventilations.